English Language Component in “Tablit” – an Innovative Kindergarten Curriculum – new opportunities for teachers - Zielińska, Urszula (Nauczyciel wczesnej edukacji kreatorem środowiska edukacyjnego dziecka, 2016)
The author focuses on the English language component in “Tablit”, an Innovative Kindergarten Curriculum, financed by the EU. English language was incorporated into the Program so that a teacher can link the scientific content incorporated in the program with the language content. This is a unique attempt at a preschool level in Poland. Due to new regulations of the Ministry of Education (May 30th, 2014), a foreign language will become obligatory for preschool children aged 5 in September 2015, while in September 2017 all children aged 3 and 4 will have compulsory foreign language classes. This constitutes a significant change in the work of a preschool teacher. “Tablit” contains an English component which can be used at very early stages of education. This component is expanded by additional games, word banks and English lesson plans. Also, the experiences and comments of teachers working with “Tablit” are presented here – a great source of inspiration for the authors of the Program.